Language contacts of Azerbaijani and Kazakh turkic languages (on the basis of azerbaijanian dialectologist, academician Mammadaga Shiraliyev’s creative works) - Huseynova, Mahira (Turkic Studies Journal, 2021)
Turkic literary languages or dialects have very long common roots, and despite various political and geographical differences, these native languages have preserved their ancient roots, vocabulary, grammatical structure, and phonetic features. Even today, the carriers of these languages can easily understand each other in a common language. Dialectological studies while speaking of the phonetic features of Turkish dialects and language varieties traditionally refer to both vowel and consonant displacements and phonetic laws. The works, monographs and articles written by scholars of Turkic peoples are also mentioned when we talk about the idea of forming a common Turkic language in our modern age. M. Shiraliyev correctly points out that on the one hand our ancient written monuments, works of our writers of the past, and on the other hand materials of the Turkic languages, help to identify phonetic events and to refine their forms. In this regard, the works of the great Azerbaijani dialectologist and Turkish scientist, academician Mammadaga Shirali oglu Shiraliyev are of great importance. The researcher made a number of words that are typical for the Turkic languages and dialects, giving a comparatively phonetic explanation. The scientist has researched specific phonetic phenomena and laws in the dialects and varieties of the Azerbaijani language and has also touched upon the integration of Kazakh language and dialects when it comes to location. M. Shiraliyev did not exclude the specific features of the numerous words used in dialects and dialects of the Azerbaijani language, compared with the literary language and dialects of the Kazakh Turkish, revealed the similarities and differences with the skills of a true dialectologist. Here, too, there were positive results.It is also clear that not only Azerbaijani dialectologists, linguists, but also world Turkology scholars have benefited and will benefit from the work of academician M.Shiraliyev. M.Shiraliyev’s research on the phonetic, morphological and lexical features of dialects and dialects of the Azerbaijani and Kazakh languages is still relevant today.